The Psychosomatic Cycle of Generalized Anxiety Disorder and Chronic Illness: A Clinical Review - Amalia Tauziah; Hafid Algristian; Asikah (Yayasan Sinergi Kawula Muda, 2026)
Generalized Anxiety Disorder (GAD) frequently coexists with chronic medical illnesses, creating a complex interaction that may intensify psychological distress and the perception of physical symptoms. This case report describes a 62-year-old male with GAD and multiple chronic comorbidities, including atherosclerotic heart disease, hypertension, type 2 diabetes mellitus with nephropathy, and benign prostatic hyperplasia. The patient presented with persistent health-related worry, sleep disturbance, and heightened preoccupation with bodily sensations, accompanied by moderate impairment in quality of life. Clinical assessment and psychological screening indicated significant anxiety symptoms without prominent depressive features. Based on clinical observations and integration with the biopsychosocial framework, somatosensory amplification, body hypervigilance, and difficulties in emotional expression were hypothesized to contribute to a psychosomatic interaction pattern. These processes may contribute to a reinforcing psychosomatic cycle in which anxiety intensifies the perception of physical symptoms, while chronic illness functions as a persistent internal stressor that maintains health-related worry. These mechanisms were not directly measured using standardized instruments but were inferred from behavioral patterns, illness narratives, and longitudinal clinical documentation. This case highlights how psychological and medical factors may mutually reinforce each other in elderly patients with multimorbidity. An integrative management approach combining pharmacological treatment, psychoeducation, and supportive psychotherapy may help interrupt this reciprocal cycle and improve functional outcomes and quality of life.